Battery slurry for lithium-sulfur battery, preparation method and application thereof
Patent Information
- Application Number
- CN202211122691.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-15
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-09-15
AI Technical Summary
锂硫电池在充放电过程中会生成可溶性的中间产物多硫化物(Lithium polysulfide,LiPS),多硫化物的溶解会导致锂硫电池中的活性物质的流失,使得循环容量下降,同时,多硫化物在电解液中的扩散会导致负极被腐蚀,致使锂硫电池迅速失效
[0014]本公开的实施例提供的技术方案可以包括以下有益效果:由于多硫化物会对酯类化合物中的酯基进行亲核进攻,发生亲核取代反应,从而在酯类化合物上接枝多硫化物,使得酯类化合物中含有高浓度的多硫化物,酯类化合物与多硫化物的反应产物对多硫化物具有排斥作用。当该电池浆料应用于锂硫电池时,对高浓度的多硫化物具有良好的抑制作用,可以抑制多硫化物的溶解及扩散,并缓解多硫化物对锂硫电池负极的腐蚀,有效提升锂硫电池的循环性能。
Smart Images

Figure CN117748052B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of battery technology, and in particular to a battery slurry, preparation method and application for lithium-sulfur batteries. Background Technology
[0002] Lithium-sulfur batteries have received widespread research and attention due to their extremely high energy density and other advantages. During the charging and discharging process, lithium-sulfur batteries generate soluble intermediate products called lithium polysulfides (LiPS). The dissolution of polysulfides leads to the loss of active materials in lithium-sulfur batteries, resulting in a decrease in cycle capacity. At the same time, the diffusion of polysulfides in the electrolyte can cause corrosion of the negative electrode, leading to rapid failure of lithium-sulfur batteries. Summary of the Invention
[0003] To overcome the problems existing in related technologies, this disclosure provides a battery slurry for lithium-sulfur batteries, a preparation method thereof, and its application.
[0004] According to a first aspect of this disclosure, a battery slurry for lithium-sulfur batteries is provided, the battery slurry comprising a first solvent and a polysulfide, the first solvent comprising one or more ester compounds having the chemical structure R1-COO-R2, wherein the molar ratio of the ester group in the ester compound to the sulfur in the polysulfide is (0.5~2.5):1.
[0005] In some embodiments of this disclosure, the molar ratio of the ester group in the ester compound to the sulfur in the polysulfide is (1~2):1.
[0006] In some embodiments of this disclosure, the polysulfide includes one or more of Li2S4, Li2S6, and Li2S8.
[0007] In some embodiments of this disclosure, R1 in the ester compound is the main chain of the ester compound, and R1 may be the same as or different from R2.
[0008] In some embodiments of this disclosure, R1 comprises a C2-C6 saturated hydrocarbon group, and R2 comprises a C1-C3 saturated hydrocarbon group.
[0009] In some embodiments of this disclosure, the battery slurry further includes a second solvent, the second solvent being used to dissolve the polysulfides; When the polysulfide is dissolved in the second solvent, the volume molar concentration of sulfur in the polysulfide in the second solvent is 0.5~2.0 mol / L.
[0010] In some embodiments of this disclosure, the second solvent includes one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, and 1,4-dioxane.
[0011] According to a second aspect of this disclosure, a method for preparing a battery slurry for lithium-sulfur batteries is provided. The method is used to prepare the battery slurry for lithium-sulfur batteries described in the first aspect of this disclosure, and the method includes: A second solvent and a polysulfide are added to the reactor, and the mixture is stirred at a first temperature for a first time under anhydrous and oxygen-free conditions to obtain a polysulfide solution. A first solvent is added to the polysulfide solution, and the mixture is stirred at a second temperature until the reaction is complete to obtain the battery slurry for lithium-sulfur batteries.
[0012] According to a third aspect of this disclosure, a coating for lithium-sulfur batteries is provided, said coating for lithium-sulfur batteries being formed by drying the battery slurry for lithium-sulfur batteries described in the first aspect of this disclosure.
[0013] According to a fourth aspect of this disclosure, a lithium-sulfur battery is provided, the lithium-sulfur battery comprising a positive electrode, a negative electrode, an electrode sheet, a separator, an electrolyte, and a coating for the lithium-sulfur battery as described in the third aspect of this disclosure, the coating for the lithium-sulfur battery being coated on the surface of the separator, the positive electrode, and / or the negative electrode.
[0014] The technical solutions provided by the embodiments of this disclosure can include the following beneficial effects: Since polysulfides can nucleophilically attack the ester groups in ester compounds, resulting in nucleophilic substitution reactions, polysulfides are grafted onto the ester compounds, leading to a high concentration of polysulfides in the ester compounds. The reaction products of the ester compounds and polysulfides have a repulsive effect on the polysulfides. When this battery slurry is applied to lithium-sulfur batteries, it has a good inhibitory effect on high concentrations of polysulfides, inhibiting the dissolution and diffusion of polysulfides and mitigating the corrosion of the lithium-sulfur battery negative electrode by polysulfides, effectively improving the cycle performance of the lithium-sulfur battery.
[0015] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Attached Figure Description
[0016] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0017] Figure 1 This is a cycle performance diagram of the lithium-sulfur battery of Embodiment 1 and Comparative Example 1 of this disclosure. Detailed Implementation
[0018] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numerals in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples of apparatuses and methods consistent with some aspects of the invention as detailed in the appended claims.
[0019] Lithium-sulfur batteries have attracted widespread research and attention due to their extremely high energy density and other advantages. Currently, ether-based electrolyte systems are commonly used in lithium-sulfur batteries, and the sulfur in various sulfur cathodes exists as traditional cyclic S8 molecules. In ether-based electrolyte systems, the electrochemical process of S8 molecules involves a multi-step lithiation process. For example, S8 molecules react with lithium stepwise to form Li₂S₈, Li₂S₆, Li₂S₄, and Li₂S₂, finally generating Li₂S, including the higher-order polysulfide Li₂S. x (x = 4~8) These polysulfides are soluble in ether-based electrolyte systems and shuttle back and forth between the positive and negative electrodes of lithium-sulfur batteries, causing irreversible loss of active materials. This leads to reduced charge / discharge efficiency and poor cycle stability. Simultaneously, dissolved polysulfides migrate to the lithium anode due to diffusion and the electric field, forming Li₂S₂ and Li₂S electronic insulating layers, causing polarization and impairing lithium-sulfur battery performance. This polysulfide "shuttle effect" results in extremely poor coulombic efficiency, which is detrimental to the long-term cycle stability of the battery.
[0020] In related technologies, methods to limit the dissolution and diffusion of polysulfides mainly involve introducing polar sites on the positive electrode or membrane, allowing for the chemisorption of polysulfides through these sites. These polar sites often possess catalytic activity, enhancing polysulfide conversion. However, the number of chemisorption sites is limited, and in the presence of high concentrations of polysulfides in the electrolyte, they cannot provide sufficient confinement. Therefore, when high concentrations of polysulfides are present, physical confinement and chemisorption are ineffective due to the concentration gradient in the electrolyte.
[0021] This disclosure provides a battery slurry for lithium-sulfur batteries, comprising a first solvent and a polysulfide. The first solvent comprises one or more ester compounds containing the chemical structure R1-COO-R2, wherein the molar ratio of the ester group in the ester compound to the sulfur in the polysulfide is (0.5~2.5):1. The polysulfide nucleophilically attacks the ester group in the ester compound, undergoing a nucleophilic substitution reaction, thereby grafting polysulfides onto the ester compound, resulting in a high concentration of polysulfides in the ester compound. The reaction product of the ester compound and the polysulfide has a repulsive effect on the polysulfides. When this battery slurry is applied to lithium-sulfur batteries, it has a good inhibitory effect on high concentrations of polysulfides, inhibiting the dissolution and diffusion of polysulfides, mitigating the corrosion of the lithium-sulfur battery cathode by polysulfides, and effectively improving the cycle performance of the lithium-sulfur battery.
[0022] An exemplary embodiment of this disclosure provides a battery slurry for lithium-sulfur batteries. The battery slurry includes a first solvent and a polysulfide. The first solvent includes one or more ester compounds containing the chemical structure R1-COO-R2, and the molar ratio of the ester group in the ester compound to the sulfur in the polysulfide is (0.5~2.5):1.
[0023] In this embodiment, the first solvent includes one type of ester compound containing the chemical structure R1-COO-R2, or several types of ester compounds with different numbers of monomers. Exemplarily, R1 in the ester compound is the main chain of the ester compound, and R1 and R2 can be the same or different. R1 may include saturated hydrocarbon groups of C2-C6, and R2 may include saturated hydrocarbon groups of C1-C3. In ester compounds containing ester groups (-COO-), since R1 is the main chain of the ester compound, the R1-CO- group has an electron-withdrawing inductive effect, making the R1-CO- group positively charged. During the nucleophilic substitution reaction, the carbon-oxygen single bond (CO) in the ester group breaks, generating an active intermediate carbocation as the R1-CO- group and a leaving group -OR2. At the same time, the R1-CO- group rapidly combines with polysulfides, causing polysulfides to be grafted onto the ester compound. This results in the ester compound containing a high concentration of structurally stable polysulfides. The reaction products of the ester compound and polysulfides have a repulsive effect on the polysulfides, effectively inhibiting the high concentration of polysulfides. The resulting battery slurry can inhibit the dissolution or diffusion of polysulfides, thereby improving the cycle performance of lithium-sulfur batteries.
[0024] The polysulfides are Li-S xThe long-chain structure of -Li allows polysulfides to act as nucleophiles in the first solvent reaction with ester compounds containing ester groups (-COO-). The lithium-sulfur single bonds (Li-S) at one or both ends of the polysulfide cleave, generating positively charged lithium ions and negatively charged Li-S ions. x -group or -S x - Group, negatively charged Li-S x -group or -S x The - group rapidly combines with the positively charged R1-CO- group in the first solvent to complete the grafting of the polysulfide, thereby making the polysulfide stably present in the ester compound. Exemplarily, the polysulfide may include one or more combinations of Li2S4, Li2S6, and Li2S8. In the battery slurry for lithium-sulfur batteries provided in this disclosure, the molar ratio of the ester group in the ester compound to the sulfur in the polysulfide is (0.5~2.5):1, preferably (1~2):1.
[0025] In some possible implementations, the battery slurry for lithium-sulfur batteries further includes a second solvent for dissolving polysulfides; when the polysulfides are dissolved in the second solvent, the volume molar concentration of sulfur in the polysulfides in the second solvent is 0.5~2.0 mol / L.
[0026] In this embodiment, the second solvent is used to dissolve the polysulfide, allowing it to dissolve and disperse, thus facilitating a nucleophilic substitution reaction between the polysulfide and the first solvent containing the ester group. The second solvent may include one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, and 1,4-dioxane. In the battery slurry for lithium-sulfur batteries provided in this disclosure, when the polysulfide is dissolved in the second solvent, the volumetric molar concentration of sulfur in the polysulfide in the second solvent is 0.5~2.0 mol / L. That is, in the battery slurry for lithium-sulfur batteries provided in this disclosure, the volume of the second solvent used to dissolve the polysulfide and the amount of the first solvent reacting with the polysulfide are limited based on the amount of sulfur in the polysulfide. For example, when the S in the polysulfide in the battery slurry used in lithium-sulfur batteries is 1 mol, the volume of the second solvent can be 0.5 L to 2 L, and the amount of ester group in the first solvent can be 0.5 mol to 2.5 mol.
[0027] In one exemplary embodiment, this disclosure provides a method for preparing a battery slurry for lithium-sulfur batteries, comprising the following steps: S1. Add the second solvent and polysulfide to the reactor, and stir at the first temperature for a first time under anhydrous and oxygen-free conditions to obtain a polysulfide solution. S2. Add the first solvent to the polysulfide solution and stir at the second temperature until the reaction is complete to obtain a battery slurry for lithium-sulfur batteries.
[0028] In step S1, the composition and mass of the selected polysulfide can be determined first. The polysulfide includes one or more of Li₂S₄, Li₂S₆, and Li₂S₈, and the amount of sulfur in the polysulfide is calculated. Then, based on the relationship between the amount of sulfur in the polysulfide and the volume of the second solvent, i.e., the volume molar concentration of sulfur in the polysulfide in the second solvent is 0.5~2.0 mol / L, the volume of the second solvent is calculated. The second solvent includes one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, and 1,4-dioxane. The polysulfide and the second solvent are added to the reactor, and stirred at a first temperature for a first time under anhydrous and oxygen-free conditions. The first temperature can be, for example, 60°C, and the first time can be, for example, 24 hours or more, to ensure that the polysulfide is fully dissolved in the second solvent and uniformly dispersed in the second solvent, thus obtaining a polysulfide solution.
[0029] In step S2, the amount of ester groups in the first solvent is calculated based on the relationship between the amount of sulfur in the polysulfide and the amount of ester groups in the first solvent, i.e., the ratio of the amount of ester groups to the amount of sulfur in the polysulfide is (0.5~2.5):1. Since the first solvent includes one or more ester compounds with the chemical structure R1-COO-R2, where R1 is the main chain of the ester compound, R1 and R2 may be the same or different, R1 includes saturated hydrocarbon groups of C2~C6, and R2 includes saturated hydrocarbon groups of C1~C3, the selection of R1 and R2 in the first solvent and the number of monomers in the first solvent formed by the ester compounds can be determined based on the amount of ester groups, and the mass or volume of the first solvent can be calculated. The first solvent is added to a reactor containing a polysulfide solution, and stirring is performed at a second temperature, for example, 40-50°C, to allow the polysulfide and the first solvent formed by the ester compounds to undergo a nucleophilic substitution reaction until the reaction is complete, yielding a battery slurry for lithium-sulfur batteries. In battery slurries used in lithium-sulfur batteries, the reaction products of ester compounds and polysulfides have a repulsive effect on polysulfides and a good inhibitory effect on high concentrations of polysulfides.
[0030] In one exemplary embodiment, this disclosure also provides a coating for a lithium-sulfur battery, the coating being formed by drying the aforementioned battery slurry for a lithium-sulfur battery.
[0031] For example, a battery slurry for lithium-sulfur batteries is uniformly coated using an extrusion coating or roll coating process. The coated battery slurry is then dried by low-temperature drying or freeze-drying to form a coating for lithium-sulfur batteries. In the coating for lithium-sulfur batteries, the ester compounds contain a high concentration of structurally stable polysulfides, forming a high polysulfide concentration interface. Due to the high polysulfide concentration gradient at the interface, the reaction products of the ester compounds and polysulfides have a repulsive effect on the polysulfides, effectively inhibiting the high concentration of polysulfides. This allows the formed coating to suppress the dissolution or diffusion of polysulfides in the lithium-sulfur battery, thereby improving the cycle performance of the lithium-sulfur battery.
[0032] In one exemplary embodiment, this disclosure provides a lithium-sulfur battery, which includes a positive electrode, a negative electrode, an electrode sheet, a separator, an electrolyte, and the aforementioned coating for the lithium-sulfur battery, wherein the coating for the lithium-sulfur battery is applied to the surface of the separator, the positive electrode, and / or the negative electrode.
[0033] The positive electrode material in a lithium-sulfur battery can be a cyclic S8 molecule, elemental sulfur, sulfur-containing inorganic sulfides, organic disulfides, polyorganic disulfides, organic polysulfides, polysulfides, and carbon-sulfur polymers, etc. The positive electrode generally consists of the positive electrode material, a conductive agent, and a polymer binder. Since polysulfides in a lithium-sulfur battery react and escape at the positive electrode, in some embodiments, a coating for the lithium-sulfur battery can be applied to the surface of the positive electrode. Because the coating for the lithium-sulfur battery forms a high polysulfide concentration interface, the high polysulfide concentration gradient at the interface has a repulsive effect on polysulfides, effectively inhibiting the dissolution of polysulfides from the positive electrode. Furthermore, the reaction products of ester compounds and polysulfides can conduct lithium ions. Therefore, the coating for the lithium-sulfur battery has a physical confinement effect, effectively suppressing the dissolution of polysulfides from the positive electrode.
[0034] The negative electrode material in a lithium-sulfur battery can be elemental lithium metal. In some embodiments, a coating for a lithium-sulfur battery can be applied to the surface of the negative electrode. Since the coating for a lithium-sulfur battery is an interface with a high polysulfide concentration, it has a repulsive effect on polysulfides and a good inhibitory effect on high concentrations of polysulfides. This can inhibit the electrochemical deposition of polysulfides on the lithium negative electrode and alleviate the corrosion of the negative electrode by polysulfides.
[0035] A lithium-sulfur battery includes electrodes, comprising a positive electrode and a negative electrode. A separator is coated on the surface of the electrodes to wet the electrolyte, providing a pathway for lithium ions to move between the positive and negative electrodes. In some embodiments, the coating for the lithium-sulfur battery can be applied to the surface of the separator. Since the coating for the lithium-sulfur battery is an interface with a high polysulfide concentration, it has a repulsive effect on polysulfides and a good inhibitory effect on the high concentration of polysulfides in the electrolyte, thus suppressing the diffusion of polysulfides in the electrolyte.
[0036] In some embodiments, the coating for lithium-sulfur batteries can be applied simultaneously to the surfaces of the separator, the positive electrode, and / or the negative electrode to achieve multiple functions such as inhibiting the dissolution and diffusion of high concentrations of polysulfides and mitigating the corrosion of the negative electrode by polysulfides, thereby further improving the cycle performance of lithium-sulfur batteries.
[0037] For example, lithium-sulfur ion batteries can be either soft-shell or hard-shell batteries, and can be applied in fields such as mobile phones, computers, cameras, and new energy vehicles to meet market and application demands.
[0038] To make the technical solutions and beneficial effects of this disclosure clearer, the battery slurry, preparation method and application of this disclosure for lithium-sulfur batteries will be described in detail below with reference to specific embodiments.
[0039] Example 1 A second solvent and a polysulfide are added to a reactor, and the mixture is stirred at 60°C for more than 24 hours under anhydrous and oxygen-free conditions to obtain a polysulfide solution. A first solvent is then added to the polysulfide solution, and the mixture is stirred at a second temperature until the reaction is complete, yielding a battery slurry for lithium-sulfur batteries. The polysulfide is Li₂S₈, the second solvent is a mixture of ethylene glycol dimethyl ether and 1,3-dioxolane, with a volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane of 1:1. The sulfur concentration in the polysulfide in the second solvent is 2.0 mol / L. In the first solvent, R1 is a C₃ saturated hydrocarbon isopropyl group, and R2 is a C₁ saturated hydrocarbon methyl group. The first solvent is polymethyl methacrylate, and the molar ratio of sulfur in the polysulfide to the ester group in polymethyl methacrylate is 2:1.
[0040] The battery slurry was dried to obtain a coating for lithium-sulfur batteries, which was then applied to the negative electrode surface of the lithium-sulfur battery. The electrolyte used in the lithium-sulfur battery was a mixture of ethylene glycol dimethyl ether and 1,3-dioxolane at a volume ratio of 1:1, followed by the addition of lithium bis(trifluoromethanesulfonyl)imide to a concentration of 1.0 mol / L, and then lithium nitrate was added to control the mass fraction of lithium nitrate in the electrolyte at 2%, resulting in a clear and transparent electrolyte. The lithium-sulfur battery was assembled under an argon atmosphere, with a sulfur loading of 4.0 mg·cm³ at the positive electrode. -2The electrolyte addition amount is 40μL, and the negative electrode is a 50μm thick lithium sheet. Comparative Example 1 A commonly used lithium-sulfur battery was used as Comparative Example 1. The electrolyte used in the lithium-sulfur battery was the same as in Example 1. The lithium-sulfur battery was assembled in an argon atmosphere, and the sulfur loading of the positive electrode was 4.0 mg·cm³. -2 The electrolyte addition amount is 40 μL, and the negative electrode is a 50 μm thick lithium sheet. The only difference is that the battery slurry for lithium-sulfur batteries provided in this disclosure is not used for coating.
[0041] Constant current charge-discharge tests were performed on the full cells of Example 1 and Comparative Example 1, with two pre-cycles at 0.05C followed by cycling at 0.1C. Figure 1 As shown, the test results indicate that when the specific capacity decays to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Comparative Example 1 is only 75 cycles; the cycle life of the battery in Example 1 exceeds 100 cycles.
[0042] Example 2 The preparation method is the same as in Example 1, wherein the polysulfide is a mixture of Li₂S₆ and Li₂S₈, with a molar ratio of Li₂S₆ to Li₂S₈ of 1:1; the second solvent is ethylene glycol dimethyl ether, and the molar concentration of sulfur in the polysulfide in the second solvent is 0.5 mol / L; in the first solvent, R1 is a C₂ saturated hydrocarbon ethyl group, and R2 is a C₁ saturated hydrocarbon methyl group, and the first solvent is polymethyl acrylate, with a molar ratio of sulfur in the polysulfide to ester groups in the polymethyl acrylate of 1:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the positive electrode surface of the lithium-sulfur battery.
[0043] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Example 2 exceeded 105 cycles.
[0044] Example 3 The preparation method is the same as in Example 1, wherein the polysulfide is a mixture of Li2S4 and Li2S6, with a molar ratio of Li2S6 to Li2S8 of 1:1; the second solvent is a mixed solvent of ethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and 1,3-dioxolane, with a volume ratio of ethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and 1,3-dioxolane of 1:1:2; and the volume molar concentration of sulfur in the polysulfide in the second solvent is 1.5 mol / L; in the first solvent, R1 is a C2 saturated hydrocarbon ethyl group, R2 is a C2 saturated hydrocarbon ethyl group, and the first solvent is ethyl polyacrylate; the molar ratio of sulfur in the polysulfide to the ester group in the ethyl polyacrylate is 0.5:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the surfaces of the positive and negative electrodes of the lithium-sulfur battery.
[0045] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Example 3 exceeded 120 cycles.
[0046] Example 4 The preparation method is the same as in Example 1, wherein the polysulfide is Li2S6, the second solvent is a mixed solvent of diethylene glycol dimethyl ether, 1,3-dioxolane, and 1,4-dioxane, with a volume ratio of 1:2:1, and the sulfur in the polysulfide has a volume molar concentration of 1 mol / L in the second solvent; in the first solvent, R1 is a C2 saturated hydrocarbon ethyl group, R2 is a C3 saturated hydrocarbon propyl group, and the first solvent is polypropylene acrylate, with a molar ratio of sulfur in the polysulfide to ester groups in polypropylene acrylate of 1.5:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the surface of the separator of the lithium-sulfur battery.
[0047] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Example 4 exceeded 110 cycles.
[0048] Example 5 The preparation method is the same as in Example 1, wherein the polysulfide is Li₂S₄, the second solvent is a mixed solvent of triethylene glycol dimethyl ether and 1,3-dioxolane, the volume ratio of triethylene glycol dimethyl ether to 1,3-dioxolane is 1:2, and the volume molar concentration of sulfur in the polysulfide in the second solvent is 0.8 mol / L; in the first solvent, R1 is a C₄ saturated hydrocarbon isobutyl group, R2 is a C₁ saturated hydrocarbon methyl group, and the molar ratio of sulfur in the polysulfide to the ester group in polypropylene acrylate is 2.5:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the positive electrode and separator surfaces of the lithium-sulfur battery.
[0049] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Example 5 exceeded 98 cycles.
[0050] Example 6 The preparation method is the same as in Example 1, wherein the polysulfide is a mixture of Li₂S₄ and Li₂S₈, the second solvent is a mixture of ethylene glycol dimethyl ether and 1,3-dioxolane, the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1, and the volume molar concentration of sulfur in the polysulfide in the second solvent is 1.6 mol / L; in the first solvent, R1 is a C5 saturated hydrocarbon n-pentyl, R2 is a C2 saturated hydrocarbon ethyl, and the molar ratio of sulfur in the polysulfide to the ester group in polypropylene acrylate is 2.3:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the negative electrode and separator surfaces of the lithium-sulfur battery.
[0051] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Example 6 exceeded 100 cycles.
[0052] Example 7 The preparation method is the same as in Example 1, wherein the polysulfide is Li₂S₈, the second solvent is a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane, the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1, and the volume molar concentration of sulfur in the polysulfide in the second solvent is 1.3 mol / L; in the first solvent, R1 is a C₄ saturated hydrocarbon isobutyl group, R2 is a C₃ saturated hydrocarbon ethyl group, and the molar ratio of sulfur in the polysulfide to the ester group in polypropylene acrylate is 0.7:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the positive electrode, negative electrode, and separator surfaces of the lithium-sulfur battery.
[0053] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Example 7 exceeded 115 cycles.
[0054] Example 8 The preparation method is the same as in Example 1, wherein the polysulfide is Li₂S₄, the second solvent is a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane, the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1, and the volume molar concentration of sulfur in the polysulfide in the second solvent is 2 mol / L; in the first solvent, R1 is a C6 saturated hydrocarbon isohexyl group, R2 is a C1 saturated hydrocarbon methyl group, and the molar ratio of sulfur in the polysulfide to the ester group in polypropylene acrylate is 2.1:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the negative electrode surface of the lithium-sulfur battery.
[0055] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Example 8 exceeded 95 cycles.
[0056] Example 9 The preparation method is the same as in Example 1, wherein the polysulfide is Li₂S₆, the second solvent is a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane, the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1, and the volume molar concentration of sulfur in the polysulfide in the second solvent is 0.6 mol / L; in the first solvent, R1 is a C₄ saturated hydrocarbon isobutyl group, R2 is a C₂ saturated hydrocarbon ethyl group, and the molar ratio of sulfur in the polysulfide to the ester group in polypropylene acrylate is 1.9:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the surfaces of the positive and negative electrodes of the lithium-sulfur battery.
[0057] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the battery in Example 9 exceeded 105 cycles.
[0058] Example 10 The preparation method is the same as in Example 1, wherein the polysulfide is a mixture of Li₂S₆ and Li₂S₈, the second solvent is a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane, the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1, and the volume molar concentration of sulfur in the polysulfide in the second solvent is 1.4 mol / L; in the first solvent, R1 is a C₃ saturated hydrocarbon isopropyl group, R2 is a C₃ saturated hydrocarbon isopropyl group, and the molar ratio of sulfur in the polysulfide to the ester group in polypropylene acrylate is 1.2:1. The battery slurry is dried to obtain a coating for lithium-sulfur batteries, which is then applied to the negative electrode surface of the lithium-sulfur battery.
[0059] The full battery was subjected to constant current charge-discharge tests, with two pre-cycles at 0.05C followed by cycling at 0.1C. The test results showed that when the specific capacity decayed to 50% of the initial specific capacity at 0.1C, the cycle life of the Example 10 battery exceeded 105 cycles.
[0060] Therefore, the coating for lithium-sulfur batteries prepared from the battery slurry provided in this disclosure has a repulsive effect on polysulfides and a good inhibitory effect on high concentrations of polysulfides. It can be found that when the battery slurry for lithium-sulfur batteries provided in this disclosure is applied to lithium-sulfur batteries, it can significantly reduce the solubility of polysulfides and inhibit the dissolution of polysulfides at the positive electrode, significantly reduce the reactivity of dissolved polysulfides with metallic lithium, improve the cycle performance of lithium-sulfur batteries, and has broad application prospects.
[0061] Other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of the invention are indicated by the following claims.
[0062] It should be understood that the present invention is not limited to the precise structure described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A battery slurry for lithium-sulfur batteries, characterized in that, The battery slurry includes a first solvent and a polysulfide. The first solvent includes one or more ester compounds containing the chemical structure R1-COO-R2, and the molar ratio of the ester group in the ester compound to the sulfur in the polysulfide is (0.5~2.5):
1. Wherein, R1 includes saturated hydrocarbon groups of C2 to C6, and R2 includes saturated hydrocarbon groups of C1 to C3.
2. The battery slurry for lithium-sulfur batteries according to claim 1, characterized in that, The molar ratio of the ester group in the ester compound to the sulfur in the polysulfide is (1~2):
1.
3. The battery slurry for lithium-sulfur batteries according to claim 1, characterized in that, The polysulfides include one or more of Li2S4, Li2S6, and Li2S8.
4. The battery slurry for lithium-sulfur batteries according to claim 1, characterized in that, R1 in the ester compound is the main chain of the ester compound, and R1 may be the same as or different from R2.
5. The battery slurry for lithium-sulfur batteries according to any one of claims 1 to 4, characterized in that, The battery slurry also includes a second solvent, which is used to dissolve the polysulfide; When the polysulfide is dissolved in the second solvent, the volume molar concentration of sulfur in the polysulfide in the second solvent is 0.5~2.0 mol / L.
6. The battery slurry for lithium-sulfur batteries according to claim 5, characterized in that, The second solvent includes one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, and 1,4-dioxane.
7. A method for preparing a battery slurry for lithium-sulfur batteries, characterized in that, The preparation method is used to prepare the battery slurry for lithium-sulfur batteries as described in any one of claims 1 to 6, the preparation method comprising: A second solvent and a polysulfide are added to the reactor, and the mixture is stirred at a first temperature for a first time under anhydrous and oxygen-free conditions to obtain a polysulfide solution. A first solvent is added to the polysulfide solution, and the mixture is stirred at a second temperature until the reaction is complete to obtain the battery slurry for lithium-sulfur batteries.
8. A coating for lithium-sulfur batteries, characterized in that, The coating for lithium-sulfur batteries is formed by drying the battery slurry for lithium-sulfur batteries as described in any one of claims 1 to 6.
9. A lithium-sulfur battery, characterized in that, The lithium-sulfur battery includes a positive electrode, a negative electrode, an electrode sheet, a separator, an electrolyte, and a coating for a lithium-sulfur battery as described in claim 8, wherein the coating for a lithium-sulfur battery is applied to the surface of the separator, the positive electrode, and / or the negative electrode.
Citation Information
Patent Citations
Lithium-sulfur battery electrolyte containing negative electrode protection solvent
CN113871719A
Intercalation anode protection for cells with dissolved lithium polysulfides
US20060194115A1